2021
DOI: 10.3389/fneur.2021.649021
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Imaging Mechanisms of Fatigue After Mild Ischemic Stroke: An Exploratory Study From a Single Chinese Center

Abstract: Objective: To explore the biochemical risk factors and imaging mechanisms of post fatigue after mild ischemic stroke among a Chinese population.Methods: Forty consecutive patients with mild ischemic stroke within onset of 14 ± 2 days were enrolled between March and June 2018. The clinical information, scale data, biomarkers in peripheral venous blood, and imaging data during hospitalization and follow-up period were collected.Results: Patient age (range 34–78) was positively correlated with the prevalence of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Twenty-nine studies (n = 3709 participants) assessed whether lesion lateralization was associated with PSF. 9, Of these, 24 showed no association, 3 reported a higher prevalence of PSF with right-sided stroke, 29,34,38 and 1 showed a higher prevalence of PSF in right-sided stroke at 6-month follow-up but not at baseline. 43 One study reported higher rates of general and mental fatigue in those with left-sided lesion lateralization.…”
Section: Associations Of Psf With Specific Neuroimaging Variablesmentioning
confidence: 97%
See 4 more Smart Citations
“…Twenty-nine studies (n = 3709 participants) assessed whether lesion lateralization was associated with PSF. 9, Of these, 24 showed no association, 3 reported a higher prevalence of PSF with right-sided stroke, 29,34,38 and 1 showed a higher prevalence of PSF in right-sided stroke at 6-month follow-up but not at baseline. 43 One study reported higher rates of general and mental fatigue in those with left-sided lesion lateralization.…”
Section: Associations Of Psf With Specific Neuroimaging Variablesmentioning
confidence: 97%
“…Seven studies assessed brainstem lesions. 29,33,38,44,47,48,51 1131 One found fewer brainstem lesions in the fatigued group. 47 Another showed thalamus and/or brainstem lesions were associated with increased PSF risk.…”
Section: Brainstemmentioning
confidence: 98%
See 3 more Smart Citations